Students’ Responses in Learning Listening Using Travel Vlog - Utami, Anisa Putri; Efransyah (PROJECT (Professional Journal of English Education), 2025)
The use of ICT in daily life is familiar to the students because they can access it easily. One of media that can attract the students is travel vlog. Travel vlog is authentic media that influence the students’ learning experiences and outcomes in language classroom. This study raised the case regarding the students’ responses to learning listening skills through the use of travel vlog. This study used a descriptive quantitative method as it allows the researcher to find the percentage of the result. The participants were tenth grade students from class X-4 from one of senior high school in Cimahi, which consisted of 34 students. The data was carried out by research questionnaires consisting of 16 close-ended questions, which were analyzed using a Likert scale. This research has been done by distributing questionnaire in form google form to the students after they learned listening recount text using travel vlog in the classroom. This research found that travel vlog can be used as learning media in learning listening, as demonstrated by the result of the questionnaire. Finding indicates that the students generally perceive travel vlog positively, citing convenience in access and use, listening learning benefit, enhance the students’ motivation, and provide students’ enjoyment . It can be concluded that integrating travel vlogs into language learning can enhance the students’ excitement and motivation in learning listening.